Ethyl 2-(4-benzyl-3-methyl-6-oxo-1,6-dihydropyridazin-1-yl)acetate: crystal structure and Hirshfeld surface analysis - Zaoui, Younes; Ramli, Youssef; Taoufik, Jamal; Mague, Joel T.; Jotani, Mukesh M.; Tiekink, Edward R. T. *; Ansar, M'hammed (International Union of Crystallography, 2019)
The title compound, C16H18N2O3, is constructed about a central oxopyridazinyl ring (r.m.s. deviation = 0.0047 A˚ ), which is connected to an ethylacetate group at the N atom closest to the carbonyl group, and benzyl and methyl groups second furthest and furthest from the carbonyl group, respectively. An approximately orthogonal relationship exists between the oxopyridazinyl ring and the best plane through the ethylacetate group [dihedral angle = 77.48 (3)]; the latter lies to one side of the central plane [the Nr—Nr—Cm—Cc (r = ring, m = methylene, c = carbonyl) torsion angle being 104.34 (9)]. In the crystal, both H atoms of the N-bound methylene group form methylene-C—HO(ring carbonyl) or N(pyridazinyl) interactions, resulting in the formation of a supramolecular tape along the a-axis direction. The tapes are assembled into a three-dimensional architecture by methyl- and phenyl-C—HO(ring carbonyl) and phenyl-C— HO(ester carbonyl) interactions. The analysis of the calculated Hirshfeld surface indicates the dominance of HH contacts to the overall surface (i.e. 52.2%). Reflecting other identified points of contact between molecules noted above, OH/HO (23.3%), CH/HC (14.7%) and NH/HN (6.6%) contacts also make significant contributions to the surface.